Order management system capabilities, benefits and value - Kyyrö, Mikko (2024)
Order management systems (OMS) are an essential part of digital commerce, responsible for overseeing the entire order lifecycle and an effective OMS can generate value for digital commerce business in several ways. Understanding what OMS is and what key capabilities the system can provide are essential for researching what type of value can be gained with an order management system. The research of order management domain is relatively underrepresented in the information systems field creating an opportunity for establishing a general definition for OMS. The thesis consisted of two parts. In the first part, a definition and a generic system flow were established by performing a literature review on OMS and related domains, reviewing OMS products in current market and combining the discoveries. The second part of thesis reviewed the literature related to information system value generation and value or benefits of processes related to OMS capabilities. Empirical research was conducted as quantitative research where the value of OMS key capabilities was studied via survey sent to digital commerce professionals in Europe and US. The key capabilities included inventory visibility, omni-channel features, order sourcing, order orchestration and order fulfillment. The results suggest that several OMS capabilities could generate high value for businesses. The capabilities had direct and indirect implications on perceived benefits and business value with increase in both online and offline sales, product return prevention, fulfillment process cost optimization and customer satisfaction.